2010
DOI: 10.1002/humu.21178
|View full text |Cite
|
Sign up to set email alerts
|

Mutations and polymorphisms in the gene encoding regulatory subunit type 1-alpha of protein kinase A (PRKAR1A): an update

Abstract: PRKAR1A encodes the regulatory subunit type 1-alpha (RIa) of the cyclic adenosine monophosphate (cAMP)-dependent protein kinase (PKA). Inactivating PRKAR1A mutations are known to be responsible for the multiple neoplasia and lentiginosis syndrome Carney complex (CNC). To date, at least 117 pathogenic variants in PRKAR1A have been identified (online database: http://prkar1a.nichd.nih.gov). The majority are subject to nonsense mediated mRNA decay (NMD), leading to RIa haploinsufficiency and, as a result, activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
155
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(157 citation statements)
references
References 52 publications
1
155
0
1
Order By: Relevance
“…(13,16,pt A1) We also cross-referenced mutations associated with ACRDYS with those associated to Carney Complex, and we did not find any molecular overlap, suggesting that different substitutions lead to different and opposite effects on protein function, with consequent different clinical phenotypes. (24) PDE4D genetic defects in our series…”
Section: Prkar1a Mutation Spectrummentioning
confidence: 85%
“…(13,16,pt A1) We also cross-referenced mutations associated with ACRDYS with those associated to Carney Complex, and we did not find any molecular overlap, suggesting that different substitutions lead to different and opposite effects on protein function, with consequent different clinical phenotypes. (24) PDE4D genetic defects in our series…”
Section: Prkar1a Mutation Spectrummentioning
confidence: 85%
“…160980). [30][31][32] This complex is characterized by pigmented lesions of the skin and mucosae, myxomas, endocrine tumors or overactivity and schwannomas. The patient of Blyth et al 13 was reported with Carney Complex Plus syndrome, indicating that not all her phenotypic characteristics could be explained by Carney Complex.…”
Section: Endocrinologic Abnormalitiesmentioning
confidence: 99%
“…The variant p.E257K (c.769G>A; g.114278G>A; NM_002734) was identified in case A, and the intronic variant g.101770A>G (NM_002734), that is predicted to abolish an acceptor splice site, was identified in case C. Both mutations have been previously associated with CNC (8,9).…”
Section: Resultsmentioning
confidence: 87%